2020
DOI: 10.2106/jbjs.19.01278
|View full text |Cite
|
Sign up to set email alerts
|

Closed Vs. Open Reduction/Salter Innominate Osteotomy for Developmental Hip Dislocation After Age 18 Months

Abstract: Background: Despite widespread use of single-stage open reduction and pelvic osteotomy for treatment of developmental dysplasia of the hip (DDH) after walking age, this aggressive strategy remains controversial. We directly compared dislocated hips treated with closed reduction (CR) to those treated with open reduction and Salter innominate osteotomy (OR/IO) to estimate the relative hazard of total hip arthroplasty (THA) and the THA-free survival time. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
2
13
1
Order By: Relevance
“…There are only three long-term studies on the Salter osteotomy in the literature. Bohm et al reported outcomes at a mean 30 years after pelvic osteotomy, Thomas et al reported Dr. Salter’s original cohort at mean 43 years following surgery, and Scott et al reported outcomes at a mean of 45 years after either closed reduction or open reduction with Salter innominate osteotomy [ 7 , 28 , 29 ]. All studies showed between 77 and 100% survivorship at 30 and 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…There are only three long-term studies on the Salter osteotomy in the literature. Bohm et al reported outcomes at a mean 30 years after pelvic osteotomy, Thomas et al reported Dr. Salter’s original cohort at mean 43 years following surgery, and Scott et al reported outcomes at a mean of 45 years after either closed reduction or open reduction with Salter innominate osteotomy [ 7 , 28 , 29 ]. All studies showed between 77 and 100% survivorship at 30 and 40 years.…”
Section: Discussionmentioning
confidence: 99%
“…For more definite causative conclusions, further longitudinal studies will be needed. Furthermore, since different surgical methods and the surgical age may have different effects on the post-operative condition and subsequent development of the morphology and mechanics of the hip ( Wang et al, 2016 ; Scott et al, 2020 ) further affecting the loading conditions of the lower extremities, future studies on such effects will also be needed. On the other hand, the current study was limited to level walking.…”
Section: Discussionmentioning
confidence: 99%
“…However, perhaps this will need to be redefined or looked at from a broader perspective. 13,14 Patients who presented at 12 weeks or less were classified as an early presentation; post-12 weeks patients were classified as late. This was similar to the criteria used by Senaran et al 15 Infants below the age of six months were defined as having DDH according to the sonographic method described by Graf.…”
Section: Methodsmentioning
confidence: 99%